Prospective study on effect of Helicobacter pylori on gastroesophageal reflux disease - Sabah Jalal Shareef (Zanco Journal of Medical Sciences, 2017)
Background and objective: The Helicobacter pylori infections role in etiology of peptic ulcer is well known, but its role in gastroesophageal reflux disease is one of the important issues which has to be confirmed. We tried to find out the effect of Helicobacter pylori infection on gastroesophageal reflux disease.